2007
DOI: 10.1016/j.jtcvs.2007.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced intimal thickening of expanded polytetrafluoroethylene grafts coated with fibrin or fibrin-releasing vascular endothelial growth factor in the pig carotid artery interposition model

Abstract: Fibrin and vascular endothelial growth factor produced effects deleterious to graft healing, by increasing the narrowing at proximal anastomosis and neointimal growth beyond that seen in uncoated grafts. It may reflect direct activation by exogenous vascular endothelial growth factor of vascular smooth muscle cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 28 publications
4
29
2
Order By: Relevance
“…Synthetic, non-degradable polymers can exhibit the opposite trend: strong mechanical properties, but poor biocompatibility. 33,49 We first showed that smooth muscle cell viability on the electrospun scaffolds investigated was not strongly dependent on scaffold processing (Fig. 3).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Synthetic, non-degradable polymers can exhibit the opposite trend: strong mechanical properties, but poor biocompatibility. 33,49 We first showed that smooth muscle cell viability on the electrospun scaffolds investigated was not strongly dependent on scaffold processing (Fig. 3).…”
Section: Discussionmentioning
confidence: 94%
“…Unfortunately, in vivo small (<6 mm)-diameter synthetic grafts often exhibit compliance mismatch, rapid plaque formation, and occlusion of the lumen. 33,49 To provide a replacement vessel with biomimetic function and properties, tissue-engineering strategies have been investigated such as cell sheets or cells cultured on biopolymers, such as collagen, to form engineered vessels. 11,21,50 A key component of these strategies is promoting proper cell organization and orientation within the vessel, especially in the tunica media (middle layer) of the vessel.…”
Section: Introductionmentioning
confidence: 99%
“…Fibrin has been proposed as a coating: results have been either discouraging (Mooney DJ et al 1996;Kim BS et al 1998;Wake MC et al 1996) or encouraging as regards anti-adhesive action in platelets and perlecan (Mooney DJ et al 1996;Kim BS et al 1998;Wake MC et al 1996); one article reported an elastin-like recombining protein [84,85,88]. Single peptides like RGD, cyclic RGD (Mooney DJ et al 1996;Kim BS et al 1998;Wake MC et al 1996) have also been proposed, but only in vitro studies are available (Walpoth BH et al 2007;Lord MS et al 2009;Jordan SW et al 2007;Tang C et al 2009;Larsen CC et al 2007).…”
Section: Permanent Materialsmentioning
confidence: 99%
“…4 Current synthetic, small diameter (<6 mm) coronary grafts frequently become occluded due to early thrombosis (blood clots) and late intimal hyperplasia (thickening of the inner wall of the vessel). 5 To prevent thrombosis and hyperplasia, a human endothelial layer can be formed on the luminal surface of the synthetic graft via inoculation of endothelial cells. 6 To possess the proper strength of adhesion and function, these cells must be grown on a substrate that inherently favors adhesion, organization and specific cell-cell communication.…”
Section: Introductionmentioning
confidence: 99%